Thickening of natural rubber latex by zinc/ammine system - Kalyani Liyanage N M V; Wijesinghe U (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p38)
It is known that when ammonia preserved NR latex is compounded with zinc oxide and an ammonium salt it often undergoes progressive thickening. The rate of zinc oxide thickening can be altered with the addition of fatty acid soaps. It has been found that the extent of the alteration of the rate of zinc oxide thickening is greatly dependent upon the type and level of added fatty acid soap. This observation suggests that the influence of added fatty acid soaps upon the thickening of NR latex by zinc/ammine system is a balance of more than one reaction.
Keywords: Natural rubber latex; Thickening